Race, ethnicity and nuclear war : representations of nuclear weapons and post-apocalyptic worlds - Williams, Paul, 1979- (Liverpool science fiction texts and studies ;, 2011)
Ranging across novels and poetry, critical theory and film comics and speeches, this title explores how writers, thinkers and filmmakers have unanswered the question: are nuclear weapons 'white'?